2017
DOI: 10.1016/j.brainres.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

The language of arithmetic across the hemispheres: An event-related potential investigation

Abstract: Arithmetic expressions, like verbal sentences, incrementally lead readers to anticipate potential appropriate completions. Existing work in the language domain has helped us understand how the two hemispheres differently participate in and contribute to the cognitive process of sentence reading, but comparatively little work has been done with mathematical equation processing. In this study, we address this gap by examining the ERP response to provided answers to simple multiplication problems, which varied bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 62 publications
(77 reference statements)
5
33
2
Order By: Relevance
“…5 ) revealed the typical sensory components (P1-N1-P2) in both tasks after the onset of either the solution or the drawing. In the digit task, a subsequent P300 response is visible for correct solutions consistent with Dickson et al (2018) ; Dickson and Federmeier (2017) ; Dickson and Wicha (2019) , and Jasinski and Coch (2012) . In contrast, in the word-picture task an N400 is visible for both match and mismatch trials peaking around 400 ms after picture onset.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…5 ) revealed the typical sensory components (P1-N1-P2) in both tasks after the onset of either the solution or the drawing. In the digit task, a subsequent P300 response is visible for correct solutions consistent with Dickson et al (2018) ; Dickson and Federmeier (2017) ; Dickson and Wicha (2019) , and Jasinski and Coch (2012) . In contrast, in the word-picture task an N400 is visible for both match and mismatch trials peaking around 400 ms after picture onset.…”
Section: Resultsmentioning
confidence: 95%
“…However, some behavioral researchers have argued that the developmental transition between calculation and retrieval may happen more gradually ( LeFevre et al, 1996 ; Siegler, 1996 ). Moreover, recent neuroimaging studies with adults have reinterpreted the ERP response observed to mathematical fact expressions, implying that children might not process arithmetic like adults do ( Dickson et al, 2018 ; Dickson and Federmeier, 2017 ; Jasinski and Coch, 2012 ). The current study adds critical new evidence to the limited literature on the neurocognitive basis of arithmetic in elementary school children and tests whether a slower developmental trajectory toward adult-like processing has indeed been overlooked.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, when the ERP pattern was considered, an attenuation of the N400 component was obtained for related results in comparison with unrelated results. Hence, the authors observed a dissociation between decision times and ERP measures where behavioural interference was accompanied by an attenuation of the N400 amplitude (although see Dickson & Federmeier, ; and Jasinski & Coch, , for an interpretation of this N400 effect as a P300 in response to a detected target associated with a correct answer). A similar pattern of results was reported by Megías and Macizo with an addition verification task.…”
Section: Introductionmentioning
confidence: 99%